Modeling of a hybrid semi-active/passive vibration control technique. (January 2015) - Mohammadi, S; Hatam, S; Khodayari, A
In this paper a new hybrid vibration damping technique as a combination of the semi-active pulse switching technique and passive constrained layer damping is proposed as an effective vibration control method for all frequency ranges. The semi-active pulse switching technique is an effective method to damp any type of vibrations with no need for external energy sources. However, its performance in high-frequency ranges decreases. In addition, passive techniques are not so effective in low-frequency ranges, but have significant effects in high-frequency ranges. The proposed hybrid damping technique as a combination of these two control methods is a new effective control technique for all frequency ranges. It covers the weakness of the semi-active method and provides significant damping in both low and high-frequency vibrations.